Colonic Intramural Hematoma in a Cat: A Case Report - Hsu, Ti-Chiu; Lin, Lee-Shuan; Chung, Cheng-Shu; Chiang, Chuan; Chiu, Hsien-Chieh; Huang, Ping-Hsun (Frontiers in Veterinary Science, 2022)
Colonic intramural hematoma is a rare condition in humans and companion animals. Its clinical presentation in cats has not previously been reported. An 8-year-old male American shorthair cat presented with acute onset of constipation and anorexia for three days. Laboratory examination indicated mild elevation of alanine aminotransferase, globulin, and total protein levels. The complete blood count was normal. Radiographs revealed a soft tissue opacity mass located caudodorsal to the urinary bladder, causing narrowing of the descending colonic lumen. Sonographically, a heteroechogenic intraluminal mass containing liquefied content was noted between the submucosal and muscular layers of the descending colon. On computed tomographic images, the mass contained two different attenuating contents with an interface. Colonoscopy was then performed for intestinal biopsy, and the contents observed in the intraluminal mass were drained via surgical evacuation and considered blood clots. Supportive medical treatment including antibiotics and fecal softener was administered, and the clinical signs were uneventfully resolved. Mild chronic proctitis without apparent malignancy was confirmed histopathologically, and no recurrence was observed after more than 14 months, thus colonic intramural hematoma was presumptively diagnosed. Information provided by multimodal imaging of the mass was essential for diagnosis and determining treatment in this case.